Spatiotemporal Analysis of Land Use / Land Cover in Swat, Pakistan Using Supervised Classification in Remote Sensing: 2000 to 2015: Spatiotemporal Analysis of Land Use / Land Cover in Swat, Pakistan Using Supervised Classification in Remote Sensing: 2000 to 2015 - Talib, Bushra; Arif, Hania; Shahzad , Muhammad; Mahmood, Syed Amer; Batool, Hafsah; Naeem, Kashif; Batool, Saira; Nasir , Jawad; Shafiq, Muhammad (International Journal of Economic and Environmental Geology, 2024)
SHORT COMMUNICATION Spatiotemporal Analysis of Land Use / Land Cover in Swat, Pakistan Using Supervised Classification in Remote Sensing: 2000 to 2015